2009
DOI: 10.1093/ndt/gfp494
|View full text |Cite
|
Sign up to set email alerts
|

NSF after Gadovist exposure: a case report and hypothesis of NSF development

Abstract: So far no cases of nephrogenic systemic fibrosis (NSF) have been published on macrocyclical gadolinium-based contrast media (Gd-CM), assumed as low NSF risk CM due to their complex stability. In our haemodialysis-dependent patient, the first symptoms indicating NSF appeared about 16 months after the exposure to Gadovist, a macrocyclical Gd-CM, and 1 month after x-ray angiography with iodinated CM (Ultravist). This indicates that in addition to excretory renal failure and Gd-CM exposure, the loss of biosyntheti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 8 publications
1
21
0
Order By: Relevance
“…In this regard, although gadobutrol is a macrocyclic agent and thus widely considered one of the "safer" GBCAs, cases of NSF following its sole injection have been reported. 23,24 Our study suggests that gadobutrol, though reported to have slightly higher relaxivity compared with established standard relaxivity agents, 11,25 provides little or no benefit over other GBCAs for brain tumor imaging when compared specifically with the imaging performance achieved with 0.1 mmol/kg of gadobenate dimeglumine. In support of this conclusion, the package insert for gadobutrol describes an as yet unpublished comparison of gadobutrol and gadoteridol and states that "performances of Gadavist and gadoteridol for visualization parameters were similar.…”
Section: Discussionmentioning
confidence: 76%
“…In this regard, although gadobutrol is a macrocyclic agent and thus widely considered one of the "safer" GBCAs, cases of NSF following its sole injection have been reported. 23,24 Our study suggests that gadobutrol, though reported to have slightly higher relaxivity compared with established standard relaxivity agents, 11,25 provides little or no benefit over other GBCAs for brain tumor imaging when compared specifically with the imaging performance achieved with 0.1 mmol/kg of gadobenate dimeglumine. In support of this conclusion, the package insert for gadobutrol describes an as yet unpublished comparison of gadobutrol and gadoteridol and states that "performances of Gadavist and gadoteridol for visualization parameters were similar.…”
Section: Discussionmentioning
confidence: 76%
“…So far, it appears that NSF has not been unequivocally confirmed in patients who have a clear medical record of only having received macrocyclic contrast agents (unconfounded) [288,302]. There is one case study report of a patient with end stage renal failure who developed NSF like symptoms 16 months after receiving Gadovist (Gadobutrol) [303]. However, debates have continued as to whether this was indeed a true case of NSF [304].…”
Section: Nephrogenic Systemic Fibrosis (Nsf)mentioning
confidence: 99%
“…where BMA = bis-(methylamide)) and far fewer diseases have been reported in patients treated with Magnevist (Gd(DTPA)), and only a few cases have been observed after the use of macrocyclic agents [160,164,[170][171][172][173][174].…”
Section: Speciation Of Mri Contrast Agentsmentioning
confidence: 99%